Integrated Household Waste Management Strategies in an Urban Community: A Case Study of Rawasari, Central Jakarta, Indonesia - Miranda Hetu Marsella; Evi Frimawaty; Sri Wahyono (Tecno Scientifica Publishing, 2026)
Waste management in densely populated urban areas is a systemic challenge, particularly in aligning community-level waste sorting processes with the capacity and capabilities of regional processing facilities. This study aimed to analyze an integrated waste management strategy at the household level, focusing on RW 01, Rawasari Village. This research employed a mixed-method approach, using material flow analysis to quantify waste generation and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to formulate waste management strategies. The results indicated that the average daily waste generation reached 0.432 kg/person/day, with a composition consisting of residual, organic, and inorganic waste. To optimize system integration, a strengthening strategy was formulated that included increasing sorting participation through multi-stakeholder collaboration, developing clear and easily understood communication, establishing incentive systems, enhancing training and early socialization, utilizing the potential of Refuse-Derived Fuel (RDF) technology to significantly reduce residual waste, and engaging stakeholders or companies to support community waste management programs. This integration strategy synergized waste management from the household scale to the regional level, contributing to the development of a circular and sustainable urban waste management system.